2023
DOI: 10.1039/d3cp01686b
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-shortened delayed fluorescence lifetime of solid-state thermally activated delayed fluorescent 4CzIPN: the structure evolution

Yarong Gu,
Xuening Sun,
Min Wu
et al.

Abstract: The incorporation of mechanochromic luminescence into thermally activated delayed fluorescence (TADF) molecule is a promising strategy for developing multifunctional mechanochromic luminescent materials. Nevertheless, due to the difficulties in systematic design,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…However, the structure–fluorescence relationships in organic rotors are underdeveloped, limiting the synthesis of bespoke fluorophores with predictable and tunable fluorescence. Recently, Yu, Gao, and Gu have reported high-pressure photophysical measurement of AIE materials supported by angle-dispersive X-ray diffraction to measure changes in unit cell dimensions. , Here, we monitor structural changes at the molecular level, correlating precise changes in molecular geometry and intermolecular distances with optical properties of AIE materials through a combination of atomically resolved X-ray crystallographic measurements and electronic spectroscopy under high pressure. We examine the structure–fluorescence relationships in Ph 7 C 7 H by tandem single-crystal X-ray diffraction, fluorescence emission spectroscopy, and UV–visible absorption spectroscopy measurements under high hydrostatic pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure–fluorescence relationships in organic rotors are underdeveloped, limiting the synthesis of bespoke fluorophores with predictable and tunable fluorescence. Recently, Yu, Gao, and Gu have reported high-pressure photophysical measurement of AIE materials supported by angle-dispersive X-ray diffraction to measure changes in unit cell dimensions. , Here, we monitor structural changes at the molecular level, correlating precise changes in molecular geometry and intermolecular distances with optical properties of AIE materials through a combination of atomically resolved X-ray crystallographic measurements and electronic spectroscopy under high pressure. We examine the structure–fluorescence relationships in Ph 7 C 7 H by tandem single-crystal X-ray diffraction, fluorescence emission spectroscopy, and UV–visible absorption spectroscopy measurements under high hydrostatic pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The computational results showed that changes in the bond length played a major role in the recombination energy of these highly conjugated aromatic molecules, and the source of the large recombination energy could be explained from the perspective of molecular orbitals; 29 researchers have also made significant efforts to improve the color purity of TADF molecules. [30][31][32][33][34][35] However, there is still a lack of theoretical research on the internal physical factors of FWHM, which hinders a true understanding of the internal mechanisms for improving color purity of luminescence molecules. Therefore, we believe that a time-saving and effective strategy is to fundamentally understand the influencing factors of FWHM through theoretical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The computational results showed that changes in the bond length played a major role in the recombination energy of these highly conjugated aromatic molecules, and the source of the large recombination energy could be explained from the perspective of molecular orbitals; 29 researchers have also made significant efforts to improve the color purity of TADF molecules. 30–35…”
Section: Introductionmentioning
confidence: 99%